Diabetic nephropathy in type 1 diabetes and pregnancy. Modern view of the problem - Ekaterina S. Shilova; Natalya V. Borovik; Maria I. Yarmolinskaya (Сахарный диабет)
Diabetic nephropathy (DN) is specific kidney damage in patients with diabetes mellitus. DN develops relatively often in pregestational diabetes patients (5,9-26%) and stills one of the main limitations for successful pregnancy in this patients’ group. Advanced DN increases risks of poor pregnancy outcomes for women and fetuses including chronic kidney disease (CKD) progression, high rate of preeclampsia, preterm deliveries, Cesarean sections, perinatal mortality and neonatal morbidity. At the same time there are more and more successful pregnancies with advanced DN in the wold.In our paper we systematize global experience of planning and management pregnancies with type 1 diabetes and DN in different stages of renal impairment. We discuss role of nephroprotective therapy in preconception care, achievement and maintaining blood pressure goals, multidisciplinary team care for improvement pregnancy outcomes in type 1 diabetic women with DN.